Effects of chromium supplementation on oxidative stress biomarkers - Amini, Mohammad Reza; Sheikhhossein, Fatemeh; Djafari, Farhang; Jafari, Alireza; Djafarian, Kurosh; Shab-Bidar, Sakineh (International journal for vitamin and nutrition research, 2023)
This systematic review and meta-analysis aimed to evaluate the effects of chromium supplementation on oxidative stress biomarkers such as superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPX), malondialdehyde (MDA), total antioxidant status (TAS), thiobarbituric acid reactive substances (TBARS), catalase (CAT), nitric oxide (NO), total antioxidant capacity (TAC) and protein carbonyl. Relevant studies, published from inception until July 2019, were searched through PubMed/Medline, Scopus, ISI Web of Science, Embase, and Google Scholar. All randomized clinical trials investigating the effect of chromium supplementation on oxidative stress were included. Out of 252 citations, 10 trials that enrolled 595 subjects were included. Chromium supplementation resulted in a significant increase in GSH (WMD: 64.79 mg/dl, 95% CI: 22.43 to 107.15; P=0.003) but no significant change in MDA, TAS, TBARS levels, SOD, CAT levels and GPX. Chromium picolinate supplementation resulted in a significant increase in TAC while failing to have a significant effect on NO. Moreover, both chromium picolinate and chromium dinicocysteinate supplementation reduced protein carbonyl levels. Overall, this meta-analysis demonstrated that chromium supplementation increased GSH without any significant changes in the mean of GPX, MDA, TAS, TBARS, CAT and SOD.